POLA SPASIO-TEMPORAL KEBAKARAN HUTAN DAN LAHAN: STRATEGI KOTA TANGGUH BERBASIS MITIGASI BENCANA DAN TATA KELOLA LAHAN DI KOTA TERPADU MANDIRI - Budi Utomo; Erni Yuniarti; Hafzhi Nur Azmi; Charmyllia; Gina Dwi Utami (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
SPATIO-TEMPORAL PATTERNS OF FOREST AND LAND FIRES: A RESILIENT CITY STRATEGY BASED ON DISASTER MITIGATION AND LAND GOVERNANCE IN AN INDEPENDENT INTEGRATED CITY Forest and land fires are a critical issue in realizing a disaster-resilient city, particularly in the Integrated Independent City (KTM) Rasau Jaya, which functions as a transmigration center and an emerging agropolitan area. This study analyzes the spatio-temporal patterns of forest and land fires from 2015 to 2024 and their relationship with land use, land tenure status, and disaster vulnerability levels. Hotspot data were obtained from NASA-MODIS satellite imagery via the SiPongi platform and analyzed using overlay (superimpose) methods and a descriptive quantitative approach. The application of the Nearest Neighbor Ratio (NNR) and Kernel Density Estimation (KDE) successfully identified clustered fire patterns in greater depth. A total of 256 hotspots were detected with an NNR value < 1, indicating a clustered spatial pattern and affirming that their distribution is not random but concentrated in vulnerable landscapes such as smallholder plantations, dry fields, and peat-dome areas. The analysis also reveals that areas with unclear land tenure—particularly state land or unregistered parcels—experience the highest fire intensity compared with land under Hak Milik (HM) or Hak Guna Bangunan (HGB), which tend to be safer due to stronger management accountability. This study recommends mitigation strategies through spatial monitoring technologies, community capacity building, and sustainable land-use management to support the transformation of KTM Rasau Jaya into a climate-resilient agropolitan city.